Analysis of the determinism of time-series extracted from social and biological systems - Luigi, Fortuna; Mattia, Frasca; Valentina, Gambuzza Lucia; Angelo, Sarra Fiore; Ali, Ramzy S.; Rashid, Mofeed T. (Iraqi Journal for Electrical and Electronic Engineering, 2010)
Self-organizing systems arise in many different fields. In this work we analyze data from social and biological systems. A central question is to demonstrate the presence of the determinism in time-series extracted from such systems that appear apparently not correlated but that are two good benchmarks for the study of complexity in real systems. We will apply the Kaplan test and we will define an order parameter for the biological data to characterize the complexity of the system.